PENEMUAN HUKUM CERAI GUGAT OLEH HAKIM PADA PENGADILAN AGAMA BERDASAR PARADIGMA POST-POSITIVISME - Muhammad Helmi (Asy-Syari'ah, 2021)
This study aims to guide judges to the Religious Courts in realizing substantive justice about divorce decisions. Based on the Presidential Instruction on the Compilation of Islamic Law and the books of fiqh, if the wife filed for divorce, then she did not get a living from the ex-husband. However, there is a rule of a Supreme Court Circular, the rule is a wife filed for divorce, but she got a living from her ex-husband except for nusyus. The method is normative juridical with a paradigmatic study of Guba and Lincoln. In the ontology of the postpositivism paradigm, the judge views reality as imperfect rules. Therefore, the judge is obliged to explore the laws that live in the community. Epistemology is a rule that has limitations so that it adapts to situations and conditions, but judges must remain objective. The methodology goes from verification to falsification. Because the judge needs to criticize and falsify the injustice that occurs at trial for the wives, for example, the husband of a civil servant feels that he is difficult by the rules, so he orders his wife to sue for divorce which results in not getting a living from her ex-husband